2014
DOI: 10.3109/08820538.2013.874468
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Techniques for the Treatment of Recurrent Pterygium: Amniotic Membrane vs Conjunctival Autograft Combined with Mitomycin C

Abstract: Amniotic membrane combined with MMC has similar recurrence rate to CA combined with MMC, in patients with recurrent pterygium. Similar outcomes and complication rates make AMT-MMC a promising method for the treatment of recurrent pterygium cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…No study reported clinical improvement in vision after surgery, an important clinical measure; however, one trial that enrolled only participants with recurrent pterygium compared baseline and postoperative logMAR visual acuity. 27 The mean baseline logMAR VAs in eyes in the CAG group (0.2 ± 1.4, n=30) and in the AMT group (0.2 ± 1.0, n=25) were similar. The mean postoperative logMAR VAs during the follow-up period also were similar: 0.1 ± 1.3 for CAG-treated eyes and 0.1 ± 1.2 for AMT-treated eyes; mean post-surgery difference 0.00 (95% CI −0.66 to 0.66).…”
Section: Resultsmentioning
confidence: 80%
“…No study reported clinical improvement in vision after surgery, an important clinical measure; however, one trial that enrolled only participants with recurrent pterygium compared baseline and postoperative logMAR visual acuity. 27 The mean baseline logMAR VAs in eyes in the CAG group (0.2 ± 1.4, n=30) and in the AMT group (0.2 ± 1.0, n=25) were similar. The mean postoperative logMAR VAs during the follow-up period also were similar: 0.1 ± 1.3 for CAG-treated eyes and 0.1 ± 1.2 for AMT-treated eyes; mean post-surgery difference 0.00 (95% CI −0.66 to 0.66).…”
Section: Resultsmentioning
confidence: 80%
“…Eleven studies restricted enrollment to primary pterygium alone (Chen 2012; Fernández García 2012; Keklikci 2007; Kheirkhah 2011; Küçükerdönmez 2007; Liang 2012; Ozer 2009; Paes 2010; Pérez Parra 2008; Tananuvat 2004; Toker 2016), five studies restricted enrollment to recurrent pterygium alone (Aragonés Cruz 2008; Chen 2009; Katircioglu 2014; Salman 2011; Stangogiannis-Druya 2004), and three studies included participants with either primary or recurrent pterygium (Besharati 2008; Küçükerdönmez 2007a; Luanratanakorn 2006). Two of the three studies that included participants with both types of pterygium reported outcomes separately by pterygium status (Küçükerdönmez 2007a; Luanratanakorn 2006), and one presented combined results only (Besharati 2008).…”
Section: Resultsmentioning
confidence: 99%
“…All trials were reported as randomized, but 16 out of 20 trials did not describe the methods of random sequence generation, and were therefore rated as at unclear risk of bias (Aragonés Cruz 2008; Besharati 2008; Chen 2009; Chen 2012; Fernández García 2012; Katircioglu 2014; Keklikci 2007; Kheirkhah 2011; Liang 2012; Luanratanakorn 2006; Ozer 2009; Pérez Parra 2008; Perry 2000; Salman 2011; Stangogiannis-Druya 2004; Tananuvat 2004). None of the included trials reported their method of allocation concealment before randomization; we therefore judged each as having unclear risk of this type of selection bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…170 It can be administered intraoperatively or postoperatively in combination with a conjunctival autograft and amniotic membrane, yielding low recurrence and complication rates. [171][172][173][174] The intraoperative application of mitomycin C results in a high success rate; however, serious complications have been reported. 175 Its use requires strict selection of patients because of the severe symptoms associated with the uncontrolled doses, including corneal edema, corneal perforation, and scleral calcification.…”
Section: Treatmentmentioning
confidence: 99%